Histopathological Analysis of Gastric Biopsies using Updated Sydney System - Zubair, Muhammad; Afridi, Nabeel Khan; Nawaid, Muhammad Amir; Tariq, Hassan; Bajwa, Akhter Ali; Khan, Naveed (Pakistan Armed Forces Medical Journal, 2022)
Objective: To analyse histopathological findings in gastric biopsies of patients with dyspepsia using an updated Sydney System. Study Design: Retrospective longitudinal study. Place and Duration of Study: Histopathology Department, Najran Armed Forces Hospital (NAFH), Saudi Arabia, from Jan 2013 to Mar 2020. Methodology: A total of 408 cases whose gastric biopsies were included in the study, and their histological features were studied. Results: Among 408 patients included in the study, 191(46.8%) were males, and 217(53.2%) were females. The mean age was 37.0±15.0 years. A total of 343 patients showed gastritis, which was mild 152(44.3%), moderate 158(46.1%) and severe 33(9.6%), respectively. The activity was observed in 200(49.0%) patients. H.pylori infection was observed in 196(48.0%) patients and intestinal metaplasia in 9(2.2%) patients. Conclusion: Most of the cases with dyspepsia showed histological evidence of gastritis. However, a significant number of patients had no gastric mucosal abnormality. Therefore, adequate and timely treatment of H.pylori infection can significantly reduce related morbidity.